Riverine Barrier Removals Could Proliferate Biological Invasions - Ellen J. Dolan; Ismael Soto; Jaimie T. A. Dick; Fengzhi He; Ross N. Cuthbert (Global Change Biology, 2025)
Multiple stressors, such as pollution, climate change, invasive species and fragmentation, threaten global ecosystems, requiring holistic management actions. Freshwater ecosystems are disproportionately biodiverse and particularly impacted by fragmentation and biological invasions. Artificial barriers, such as dams and weirs, are long‐standing features of global landscapes, with a divergence of views on their benefits and disbenefits. Recognition of the negative impacts of barriers on the river continuum and native biota, particularly for migratory aquatic species, has led to a rapid rate of barrier removals in recent decades, especially in North America and Europe. However, since the rise in riverine barrier construction centuries ago, global biological invasion rates have concurrently surged. Artificial barriers can paradoxically slow the spread of invasive species through freshwaters, and barrier removal efforts thus risk proliferating invasive species that disperse rapidly through connected habitats. Despite well‐intended plans for river restoration through barrier removals, the subsequent spread and colonisation of invasive species have been largely overlooked. This presents a ‘connectivity conundrum’: the removal of barriers intuitively addresses the issues of native species migrations and dispersals, but could perversely exacerbate the spread of invasive species. Basin‐scale data collection around the short‐ and long‐term impacts on invasive species will help to underpin future restoration projects and maximise the potential beneficial outcomes of barrier removals for native species.